1980
DOI: 10.1037/h0077645
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of maternal transport by Norway rat pups.

Abstract: Norway rat young assume a characteristic posture as they are being transported to a new nest. This transport response is normally elicited by the tactile stimulation received from the mother's teeth on the dorsal and lateral skin. The pup transport response develops gradually over the first 10 days of life and can then be reliably elicited until the third week after which the response becomes more difficult to stimulate. The response, therefore, is seen during the time that mothers-carry relatively large pups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 7 publications
4
74
1
Order By: Relevance
“…Instead, the mother mouse uses her mouth to grasp a bit of skin at the back of the mouse pup's neck (Figure 2). Researchers were able to recreate this grip by pinching this same spot [3][4][5][6]. This way, the researchers had more control over the experiment.…”
Section: How Does the Tr Work?mentioning
confidence: 99%
“…Instead, the mother mouse uses her mouth to grasp a bit of skin at the back of the mouse pup's neck (Figure 2). Researchers were able to recreate this grip by pinching this same spot [3][4][5][6]. This way, the researchers had more control over the experiment.…”
Section: How Does the Tr Work?mentioning
confidence: 99%
“…When a pup is grasped for transport by the mother, the pup characteristically responds by reducing its general activity (i .e ., by reducing its struggling) and then actively flexes and adducts its hindlimbs and extends and adducts its forelimbs as the mother grasps the nape of its neck. The ecological value of the pup's response is that it produces a compact package for transport (Brewster & Leon, 1980). The transport response in the infant is most effectively elicited by the mother's grasping the infant's dorsal surface, but it can also be induced by the experimenter's pinch on the infant 's dorsal surface (Brewster & Leon, 1980).…”
Section: Sam Houston State University Huntsville Texasmentioning
confidence: 99%
“…The ecological value of the pup's response is that it produces a compact package for transport (Brewster & Leon, 1980). The transport response in the infant is most effectively elicited by the mother's grasping the infant's dorsal surface, but it can also be induced by the experimenter's pinch on the infant 's dorsal surface (Brewster & Leon, 1980). Wilson (1988) has reported that when a grasp or pinch on a pup's dorsal surface proves to be an inadequate stimulus in producing a strong transport response, the response may be induced or potentiated by giving the pup additional tactile stimulation in the form of an air puff, water puff, or tailpinch.…”
Section: Sam Houston State University Huntsville Texasmentioning
confidence: 99%
See 2 more Smart Citations